Physiology in Extreme Conditions: Adaptations and Unexpected Reactions - Maria G. Trivella (Frontiers Research Topics, 2017)
Physiology in extreme conditions can reveal important reactions of the human body, which help our assessment of limits emerging under healthy conditions and critical signals of transition toward disease. While many mechanisms could simply be associated with adaptations, others refer to unexpected reactions in response to internal stimuli and/or external abrupt changes.